Effect of dose and release rate of CTGF and TGFβ3 on avascular meniscus healing. Issue 7 (28th March 2019) - Tarafder, Solaiman; Gulko, Joseph; Kim, Daniel; Sim, Kun Hee; Gutman, Shawn; Yang, Jian; Cook, James L.; Lee, Chang H.
ABSTRACT: Meniscus tears in the avascular region rarely functionally heal due to poor intrinsic healing capacity, frequently resulting in tear propagation, followed by meniscus deterioration. Recently, we have reported that time‐controlled application of connective tissue growth factor (CTGF) and transforming tissue growth factor β3 (TGFβ3) significantly improved healing of avascular meniscus tears by inducing recruitment and step‐wise fibrocartilaginous differentiation of mesenchymal stem/progenitor cells (MSCs). In this study, we investigated effects of the dose of CTGF and the release rate of TGFβ3 on avascular meniscus healing in our existing explant model. Our hypothesis was that dose and release rate of CTGF and TGFβ3 are contributing factors for functional outcome in avascular meniscus healing by stem cell recruitment. Low (100 ng/ml) and high (1, 000 ng/ml) doses of CTGF as well as fast (0.46 ± 0.2 ng/day) and slow (0.29 ± 0.1 ng/day) release rates of TGFβ3 were applied to our established meniscus explant model for meniscus tears in the inner‐third avascular region. The release rate of TGFβ3 was controlled by varying compositions of poly(lactic‐co‐glycolic acids) (PLGA) microspheres. The meniscus explants were then cultured for 8 weeks on top of mesenchymal stem/progenitor cells (MSCs). Among the tested combinations, we found that a high CTGF dose and slow TGFβ3 release are most effective for integrated healing of avascular meniscus, demonstrating improvements in alignment of collagen fibers, fibrocartilaginous matrix elaboration and mechanical properties. This study may represent an important step toward the development of a regenerative therapy to improve healing of avascular meniscus tears by stem cell recruitment. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1555–1562, 2019.